Answer :

Let a be the first term and d be the common difference.


Given: a7 = - 1


a16 = 17


Now, Consider a7 = - 1


a + 6d = - 1 …………(1)


Consider a16 = 17


a + 15d = 17 …………(2)


Subtract equation (1) from (2), we get,


9d = 18


d = 2


Common difference = d = 2


Now, from equation (1), we get,


a = - 1 - 6d


= - 1 - 6(2)


= - 13


Now, nth term of the AP is given by


an = a + (n - 1)d


= - 13 + (n - 1)2


= 13 + 2n - 2


= 2n - 15

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses